Let α , β ∈ R be such that x → 0 lim α x − sin x x 2 sin ( β x ) = 1 . Then 6 ( α + β ) + 2 = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Best solution of all 3, I guess, I mean , its easier than applying series.
Using Taylor expansion : sin x = n = 0 ∑ ∞ ( 2 n + 1 ) ! x 2 n + 1 ( − 1 ) n
L = x → 0 lim α x − sin x x 2 sin β x = x → 0 lim α x − ( x − 3 ! x 3 + ⋯ ) x 2 ( β x − 3 ! β 3 x 3 + ⋯ ) = x → 0 lim x 2 α − 1 + 3 ! 1 + ⋯ β − 3 ! β 3 x 2 + ⋯
This forces α = 1 ,
L = x → 0 lim 3 ! 1 β = 1
Thus β = 6 1 making the answer 6 ( α + β ) + 2 = 9
Can you make an alternative in this solution only with L'Hospital's Rule?
Log in to reply
L-Hopital would be difficult to apply here, some limits are traditionally made to be solved by series
Relevant wiki: Maclaurin Series
L = x → 0 lim α x − sin x x 2 sin ( β x ) = x → 0 lim α x − ( x − 3 ! x 3 + 5 ! x 5 − 7 ! x 7 + . . . ) x 2 ( β x − 3 ! ( β x ) 3 + 5 ! ( β x ) 5 − 7 ! ( β x ) 7 + . . . ) = x → 0 lim α x − x + 3 ! x 3 − 5 ! x 5 + 7 ! x 7 + . . . β x 3 − 3 ! β 3 x 5 + 5 ! β 5 x 7 − 7 ! β 7 x 9 + . . . = x → 0 lim 0 + 3 ! x 3 − 5 ! x 5 + 7 ! x 7 + . . . β x 3 − 3 ! β 3 x 5 + 5 ! β 5 x 7 − 7 ! β 7 x 9 + . . . = x → 0 lim 3 ! 1 − 5 ! x 2 + 7 ! x 4 + . . . β − 3 ! β 3 x 2 + 5 ! β 5 x 4 − 7 ! β 7 x 6 + . . . = 6 β Using Maclaurin series Putting α = 1 Dividing up and down by x 3
Since L = 1 , ⟹ β = 6 1 , ⟹ 6 ( α + β ) + 2 = 6 ( 1 + 6 1 ) + 2 = 9
Problem Loading...
Note Loading...
Set Loading...
Write it(L) as: L = β ⋅ x → 0 lim α x − sin x x 3 × β x sin ( β x ) 1 ( 0 0 ) Apply Lhopital rule: L = β ⋅ x → 0 lim α − cos x 3 x 2 Since numerator is tending to zero, for limit to be 1 ( = 0 ) , denominator must also tend to zero i.e α = 1 . Then :
L = 3 β ⋅ x → 0 lim 0 . 5 x 2 1 − cos x 1 = 6 β = 1 ⟹ β = 6 1
∴ 6 ( α + β ) + 2 = 9